(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2020)
This paper outlines some of the dilemmas of turning graduates from vocational education and training courses into industry-ready employees. It raises a number of questions that are ripe for action research with the context of the Boyer model of scholarship.